Graphene Oxide Nano-Concentrators Selectively Modulate RNA Trapping According to Metal Cations in Solution - Palmieri, Valentina; Di Pietro, Lorena; Perini, Giordano; Barba, Marta; Parolini, Ornella; De Spirito, Marco; Lattanzi, Wanda; Papi, Massimiliano (Frontiers in Bioengineering and Biotechnology, 2020)
With recent advances in nanotechnology, graphene nanomaterials are being translated to applications in the fields of biosensing, medicine, and diagnostics, with unprecedented power. Graphene is a carbon allotrope derived from graphite exfoliation made of an extremely thin honeycomb of sp2 hybridized carbons. In comparison with the bulk materials, graphene, and its water-soluble derivative graphene oxide, have a smaller size suitable for diagnostic platform miniaturization as well as high surface area and consequently loading of a large number of biological probes. In this work, we propose a nanotechnological method for concentrating total RNA solution and/or enriching small RNA molecules. To this aim, we exploited the unique trapping effects of GO nanoflakes in presence of divalent cations (i.e. calcium and magnesium) that make it flocculate and precipitate forming complex meshes positively charged. Here we demonstrated that GO traps can concentrate nucleic acids in the presence of divalent cations and that small RNAs can be selectively released from GO-magnesium traps. GO nano-concentrators will allow better analytical performance with samples available in small amounts and will increase the sensitivity of sequencing platforms by short RNA selection.